(untitled) (Orfeu, 2018)
This article presents a dialogue with authors of the so called Black Atlantic to introduce the necessary debate about a musical education based on the philosophical and historical knowledge and bases - historical and contemporary - of the African musical arts and the African diaspora. It points to a historical gap in the studies of Afro-Latin, Afro-Caribbean and African-American music in Latin American countries, as well as the need to build procedures and methodological foundations applied to the teaching of African (diaspora) musical arts with emphasis on the Brazilian context. The author seeks to encourage an epistemological debate, referenced by various authors from the musical and historical contexts of Africa and the African Diaspora, and to outline a theoretical framework for music education on the bases of African matrices for the most of countries and regions with black cultural and musical expressions, that in future may lead to African (African diaspora) musical and performance education and training.